Synthesis of some novel heterocyclic compounds derived from diflunisal hydrazide as potential anti-infective and anti-inflammatory agents - TATAR, ESRA; KABASAKAL, LEVENT (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2007)
Three novel series of 2',4'-difluoro-4-hydroxybiphenyl-3-carboxylic acid derivatives namely 4-substituted-1,2,4-triazoline-3-thiones (4a-g); 2-substituted- 1.3.4-thiadiazoles (5a-g) and 2-substituted- 1,3,4-oxadiazoles (6a-g) have been synthesized. Twenty-one of the newly synthesized compounds were tested against various bacteria, fungi, yeast species and virus. In addition, we have replaced the carboxylic acid group of diflunisal with heterocycles and the anti-inflammatory activity of heterocycles reported here. Compound (5d) showed activity against Escherichia coli Al and Streptococcuspyogenes ATCC-176 at a concentration of 31.25 mu g/mL, whereas cefepime, the drug used as standard, has been found less active against the bacteria mentioned above. Compound (4b) has exhibited activity against Aspergillus variecolor and Trichophyton rubrum at a concentration of 31.25 and 15.25 mu g/mL, whereas Amphotericin B, the drug used as standard, has been found less active against the yeast and fungi. The highest antiviral activity was found in the 1,3,4-thiadiazole derivative (5a) having a methyl group at 2nd position against Sindbis virus at 9.6 mu g/mL. Compound (4c) exhibited the highest anti-inflammatory activity (73.03%) whereas diflunisal, the drug used as standard, has been found less active (24.16%). Compound (5f) presented similar antinociceptive activity with the standard drug (paw withdrawal latency was 19.21 s compared to that of diflunisal which was 19.14 s, in hot plate test). (c) 2007 Elsevier Masson SAS. All fights reserved.
Keywords: 1,2.4-Triazoline-3-thione; 1,3,4-Thiadiazole; 1,3,4-Oxadiazole; diflunisal; anti-inflammatory agents; 1,3,4-THIADIAZOLE DERIVATIVES; BIOLOGICAL-ACTIVITIES; ANTIBACTERIAL; INHIBITORS; EXTRACT; DESIGN; DRUG; AIDS